PAC substitutions impact on the tobacco market in Romania - Ruxandra-Eugenia Pop (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The tobacco market in Romania has seen a significant increase regarding the size of the areas covered by this industrial crop and production. One of the key factors underpinning this statement is the volume of forms of financial support under the PAC 2014-2020 for this crop. It is well known that among the National Transitional Aid for the Vegetable Sector, the tobacco subsidy (ANT 4) provides the highest amounts per hectare cultivated. In this paper we will evaluate the relationship between production variables, existing surfaces on the tobacco market and, on the other hand, the volume of subsidies granted to us in the country using statistical analysis methods using SPSS and Microsoft Excel.
Keywords: Q15; Q52; Q27; 330; tabacco market; PAC 2014-2020; linear regression; statistical analysis